STRUGGLING TO SURVIVE IN COMPLEX AND MODERN ERA - Batubara, Chuzaemah; Fatimah, Fatimah (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2017)
The holistic implementation of Islamic law in the life of Acehnese community has brought “big changes,” one which is force the majority Acehnese involved in conflicts or disputes bringing their cases solved to Mahkamah Syari’ah as a formal legal instituon which mostly leads disputants  to expensive costs, long consumed and waste time as well as exhausting, even unjust feeling.  However, the implementation has revitalized the existence of customary court which  almost gave up in New Order regimes. The paper argues that the Acehnese legal culture embodied in Peradilan Gampông as customary Law is living law that would resolve destructive conflict and reduce the intention and huge suggestion of some people to resolve their cases through formal legal solution in State Courts (Mahkamah Syariah). With a socio-legal approach the research is focused on case studies on resolving dispute in Aceh customary courts (Peradilan Adat Gampông) at several Gompông in Aceh. The study found that peace, equilibrium, societal hood and justice as dominant principles in the life of Acehnese people at gampôngs and cities have brought customary law revived and as socities’ primary choices in resolving their legal cases.